Terrorist Groups in India: A Case Study: The Impact of Terrorist Groups in India: A Comprehensive Case Study (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The former National Security Advisor of India, M. K. Narayanan had made disclosure of as many as 800 terrorist cells operating in India with “external support” (Times of India, 12 August 2008) which reflects the extent to which terrorism has made inroads into the country as a result of outside country exporting and sponsoring terrorism to India. India continues to experience terrorist attacks launched by transnational groups based in Pakistan. (Government of United States of America 2016) According to the Country Reports on Terrorism 2012 by US, India was ranked amongst the top ten countries in world with most terrorist attacks, i.e. total 557 terrorist attacks in the year 2012. (Government of United States of America 2013)